Short and long-term studies of telomerase inhibitor compounds in human and mouse cancer cells - Reis, Melanie (2019)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2014